2007
DOI: 10.1001/archpsyc.64.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Co-occurring Cannabis Use Disorders on the Course of Bipolar Disorder After a First Hospitalization for Mania

Abstract: The effects of the sequence of onsets of bipolar and cannabis use disorders were less pronounced than observed in co-occurring alcohol and bipolar disorders. Aggressive drug abuse treatment immediately after a first psychiatric hospitalization might decrease rates of recurrence and new cases of cannabis use disorder in the course of bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
1
19

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(157 citation statements)
references
References 25 publications
6
131
1
19
Order By: Relevance
“…Weiss et al (2005) point out that SUDs tend to "wax and wane" over time in bipolar patients, and therefore should be a focus of clinical attention even if not currently problematic. For example, Strakowski et al (2007) recently reported that most bipolar patients with co-occurring cannabis use disorders had a remission following hospitalization. Nevertheless, a high rate of recurrence was observed over a 5-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Weiss et al (2005) point out that SUDs tend to "wax and wane" over time in bipolar patients, and therefore should be a focus of clinical attention even if not currently problematic. For example, Strakowski et al (2007) recently reported that most bipolar patients with co-occurring cannabis use disorders had a remission following hospitalization. Nevertheless, a high rate of recurrence was observed over a 5-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis use increases the time spent in an affective state, is associated with rapid cycling, and while the majority of cannabis use remits during hospital admission, it is rapidly reinstated following discharge (Strakowski 2007).…”
Section: Cannabis Usementioning
confidence: 99%
“…Importante observação foi relatada no estudo de Strakowski et al, que após um período de internação por um quadro de mania, há uma janela na qual estes pacientes permanecem em abstinência à maconha, e sugerem, desta forma, intervenções incisivas e precoces neste período a fim de manter estes pacientes em abstinência à droga, o que se torna um desafio, visto que a maioria dos serviços públicos não têm por hábito agendar retornos precoces a pacientes egressos de internações integrais 17 .…”
Section: Desordens Psiquiátricas Secundáriasunclassified
“…os estudos até o momento mostram mais riscos da associação da cannabis no TAB do que benefícios, conclui-se que o uso da cannabis como adjuvante no tratamento do TAB deve ser restrito aos ambientes de pesquisa, exclusivamente 17 .…”
Section: Tratamento Na Comorbidade Uso/abuso/dependência De Cannabis unclassified